Assembly of full-length cDNA, and heterologous expression, of Nudaurelia B virus RNA - Luke, Gary Joseph (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2001)
Nudaurelia beta virus (NÎ²V) is a monopartite genome virus belonging to the family Tetraviridae. Its host range has been found to be limited to a single insect order, the Lepidoptera (moths and butterflies). The single-stranded positive-sense RNA genome consists of 6625 nucleotides containing two open reading frames (ORFs). The 5' proximal ORF of 5778 nucleotides encodes a protein of 215 kDa containing three functional domains characteristic of RNA-dependent RNA polymerase. The 3' proximal ORF, of 1836 nucleotides, encodes the 66 kDa capsid precursor protein and overlaps the replicase gene by more than 99% and is in the +1 reading frame relative to the replicase reading frame. The full-length cDNA construct of the NÎ²V genome was assembled using a homologous overlapping PCR linking method. The starting material consisted of seven overlapping pieces that were constructed for sequencing. Due to the degradation of the full-length RNA obtained from virus extracted from field-collected Nudaurelia cytherea capensis larvae other alternative methods needed to be applied. Sub-cloning using restriction enzyme sites also required an alternative method being used, due to the abundance of restriction sites of the same type in the NÎ²V genome. This led to the use of a method similar to "DNA Shuffling" where overlapping pieces were connected using a modified PCR protocol. After the construction of the NÎ²V genome, the full-length PCR product was cloned and checked for large insertion and deletions that could have resulted from the PCR amplification. The heterologous expression of the NÎ²V capsid protein linked to a fusion protein (Glutathione S-transferase) in E.coli, confirmed the authenticity of the prescribed capsid gene ORF. The expression showed that the virus protein was subjected to protease digestion in DH5Î± E.coli, suggesting that the protein was insoluble in the cell cytoplasm. The capsid gene expression in a modified E.coli strain, Epicurian Coli BL21-CodonPlus (DE3)-RIL, resulted in high levels of the correct molecular weight protein with minimal degradation. The modified strain was designed for over-expression of eukaryotic protein with lowered protease activity. The above results have opened the way for further research that would yield valuable insight into the molecular biology and replication strategy of the NÎ²V in cell cultures.
Keywords: Imbrasia cytherea; RNA; Viruses; DNA